HUKUM TATA NEGARA DARURAT CORONA DI INDONESIA - Michael, Tomy (Mimbar Keadilan, 2020)
AbstractThe purpose of this study is to offer novelty regarding the emergency status issued by the Indonesian government appropriately. Using normative research with an orientation that is not based on conceptual. The initial beginnings that occurred in Indonesia resulted in changes in the application of the law, especially state administration law where an emergency had two components, namely the legal framework consisting of the constitution and the legislative basis for emergencies and the operational framework involving organizational structures and strategic plans for dealing with emergencies. In this case the government must immediately lockdown because in the principle of emergency state administration law is an absolute thing that must be done. To carry out lockdown, it requires firmness and a combined security of all parties. Lockdown must also be limited by legal norms such as a presidential decree to avoid arbitrariness by the government. Such understanding is important so that the country can run well.Keywords: corona; emergency statutory law; lossAbstrakTujuan penelitian menawarkan kebaruan terkait status kedaruratan yang dikeluarkan oleh pemerintah Indonesia secara tepat. Menggunakan penelitian normatif dengan orientasi yang tidak bersumber pada konseptual. Permulaaan awal yang terjadi di Indonesia mengakibatkan perubahan dalam penerapan hukum khususnya hukum tata negara dimana adanya keadaan darurat memiliki dua komponen yaitu kerangka hukum yang terdiri dari undang-undang dasar dan basis legislatif untuk keadaan darurat serta kerangka kerja operasional yang melibatkan organisasi struktur dan rencana strategis untuk berurusan dengan keadaan darurat. Di dalam hal ini pemerintah harus segera melakukan lockdown karena dalam prinsip hukum tata negara darurat adalah hal mutlak yang harus dilakukan. Untuk melakasanakan lockdown maka dibutuhkan ketegasan dan gabungan keamanan dari segala piha. Lockdown juga wajib dibatasi dengan norma hukum seperti keputusan presiden agar tidak timbul kesewenang-wenangan dari pemerintah. Pemahaman demikian penting agar negara dapat berjalan dengan baik.Kata kunci: corona; hukum tata negara darurat; kerugian